O papel das mulheres na conservação das áreas remanescentes de mangabeiras (Hancornia speciosa Gomes) em Sergipe. - Santos, Jane Velma dos (2007)
The extraction of mangaba developed by traditional groups has proven to be an important source of occupation, income and conservation of biodiversity. In a paradox, in a crescent context of valuation of the fruit, these groups face difficulties in accessing the native fields, which has made it hard its social reproduction and consequently the conservation of sources for extraction. In this context, the goal of this dissertation is to analyze the purpose of women in the extraction of mangaba, in the paradoxal context of crescent commercial valuation of the fruit and the increase in the difficulties in accessing the native fields in the town of Barra dos Coqueiros/SE. The methodology is formed by qualitative and quantitative approaches with the following methodological procedures: transversal walks, observations, interviews (semi-structuralized questionnaires) with the research actors in the three investigated towns: Capoã, Olhos D ÁGua e Jatobá. The main results show that: i) the extraction is an important source of occupation and income for the groups; ii) the ways to access the extraction sources will happen in three ways: in their own land, by the system of half use of common areas; iii) the participation of women in the extraction and commercialization of mangaba is predominant; iv) the work of women in the extraction and commercialization represent a breach in traditional cultural standards; v) the women have fundamental participation in the conservation of remainder mangabeiras; vi) the main knowledge dominated by the women are regarding development, fenology and plant reproduction; vii) the knowledge about the handling of the plants was passed through generations orally; viii) the mangabeiras are an endangered species because of touristic activities that have been intensified and because of real state speculation.